Vaccination to Form Immunity (Measles Immunization) as The Body's Ability to Fight Foreign Substances (Immune System) Entering the Body in Infants - Hanifah, Astin Nur; Treasa, Adisty Dwi; Andriani, Fitri; Wulandari, Bayu Larasati; Amalia, Rizki; Limbong, Kori (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Immunization is a way to actively increase a person's immunity to an antigen, so that if he or she is later exposed to a similar antigen, the disease will not occur. The main objective is to describe or create a picture of an objective state study conducted by examining a problem through a process and reducing the number of cases of illness and death due to diseases that can be prevented by immunization. This research method is a case study with a descriptive method, namely a method carried out with the main objective of describing or creating a picture of an objective state study conducted by examining a problem through a process consisting of a single unit. The results of this study can be seen that after proper and careful vaccination immunization and supported by good cooperation by the patient's family and the patient himself, with measles immunization there was no mild fever, mild respiratory tract infections and diarrhea due to proper anticipation. The conclusion obtained is that Measles Immunization at the Bontomarannu Health Center., researchers did not find harmony in regulating the implementation as a whole, to overcome fever in children, advise mothers to continue to provide nutritious food, advise mothers to continue to maintain the health and nutrition of children and advise mothers to come to health workers if there are complaints.